(untitled) (Global Journal of Computer Science and Technology, 2019)
A small baby needs parents’ attention for whole day and 7 days a week, which is impossible due to other priorities like house hold activities, official works and personal works. Day care centre or nanny is the two options available which involves lot of passion. We all live in a world where technologies are sournded all around us. The new generations of parents were raised up with this amazing technology. There are lots of things or items present on these earth that parents will buy to help them care for their baby (Cradle, Crib, Baby Monitor, etc.). So, there is a need for safe and secure place to take good care of the children2019;s need with minimum human intervention and care, which can be accomplished with the help of a 201C;Smart Baby Cradle201D;. A 201C;Smart Baby Cradle201D; provides parents a smart automatic cradle system which help these parents monitor and comfort the baby. The Smart Baby Cradle allows them to monitoring their babies, the cradle, play soothing music, even speak to the baby, observing the temperature of the infant, bed wet sensor which will caution the attendants for bunk wetting of the infant. The mother where so ever she is can have a look on the baby through camera inserted in the cradle. All the fittings are done through Arduino and PIR sensor. Additionally, we provide a predefined nutrition food chart to help baby remain healthy.